The Medroplan project: process and key lessons - Gabiña D.; Iglesias A.; López-Francos A. (Drought management guidelines technical annex, 2007)
MEDROPLAN (Mediterranean Drought Preparedness and Mitigation Planning) is a project funded through the Euro-Mediterranean Regional Programme for Local Water Management (Meda Water Programme) whose first call for proposals, launched in 2002, was to enhance regional co-operation in the areas of sustainable and integrated management of water resources through institutional strengthening, raising the awareness of society, capacity building and participation. The main final objective of the project has been to provide guidelines for drought preparedness plans, adapted to the physical and socio-economic environment of the Mediterranean countries, and elaborated following a common methodology. It is expected that the guidelines will provide partner countries with a logical and integrated approach to minimise the impacts of drought on their people and resources, and to change the way of facing drought from the present crisis management approach to proactive risk management. Another important objective of the project was to provide the framework for the setting up of a drought preparedness network for the Mediterranean countries.